The Disk Substructures at High Angular Resolution Project (DSHARP). V. Interpreting ALMA Maps of Protoplanetary Disks in Terms of a Dust Model - Birnstiel, Tilman; Dullemond, Cornelis P.; Zhu, Zhaohuan; Andrews, Sean M.; Bai, Xue-Ning; Wilner, David J.; Carpenter, John M.; Huang, Jane; Isella, Andrea; Benisty, Myriam; Pérez, Laura M.; Zhang, Shangjia (Astrophysical journal. Letters, 2018)
The Disk Substructures at High Angular Resolution Project (DSHARP) is the largest homogeneous high-resolution (∼0 035, or ∼5 au) disk continuum imaging survey with the Atacama Large Millimeter/submillimeter Array (ALMA) so far. In the coming years, many more disks will be mapped with ALMA at similar resolution. Interpreting the results in terms of the properties and quantities of the emitting dusty material is, however, a very non-trivial task. This is in part due to the uncertainty in the dust opacities, an uncertainty that is not likely to be resolved any time soon. It is also partly due to the fact that, as the DSHARP survey has shown, these disk often contain regions of intermediate to high optical depth, even at millimeter wavelengths and at relatively large radius in the disk. This makes the interpretation challenging, in particular if the grains are large and have a large albedo. On the other hand, the highly structured features seen in the DSHARP survey, of which strong indications were already seen in earlier observations, provide a unique opportunity to study the dust growth and dynamics. To provide continuity within the DSHARP project, its follow-up projects, and projects by other teams interested in these data, we present here the methods and opacity choices used within the DSHARP collaboration to link the measured intensity I to dust surface density d.